(untitled) (Analysis in Theory and Applications, 2021)
The existence of an infinite sequence of sign-changing solutions are proved for a class of quasilinear elliptic equations under suitable conditions on the quasilinear coefficients and the nonlinearity where ΩR^N is a bounded domain with smooth boundary, and we useD_iu=ux_i, D_iju=^2 ux_i x_j, and D_zb_ij(z)=ddzb_ij(z).The main interest of this paper is for the case of bounded quasilinearity b_ij. The result is proved by an elliptic regularization method involving truncations of both u and the gradient of u.